Evaluation of transverse crack initiation in interlaminar toughened CFRP cross-ply laminates under cyclic loading - Hiroyuki KAWADA; Masaki SOGA; Ko SHIGEMORI; Atsushi HOSOI; Yuzo FUJITA (Nihon Kikai Gakkai ronbunshu, 2014)
Initiation and growth behaviors of a transverse crack occurred in interlaminar toughened CFRP cross-ply laminates under cyclic loading were evaluated. Specimens whose stacking sequence is [0/904]S and [0/906]S were formed with T800S/3900-2B prepreg. The specimen edges were observed with an optical microscope and a laser microscope to investigate the behavior of transverse crack initiation and growth. To observe the edge surface of the specimen at arbitrary loading cycles, a replica technique was used. In addition, soft X-ray photography was used to observe internal damage. The number of cycles to transverse crack initiation was predicted quantitatively by applying the normalized modified Paris law, which shows the relationship between transverse crack density growth rate and normalized energy release rate range associated with transverse crack formation. Analytical results showed good agreement with experimental results. It was found that transverse crack initiation in interlaminar toughened CFRP laminates can be evaluated by applying the normalized modified Paris law. Moreover, in comparison to the laminates with and without toughened layers, the fatigue life to transverse crack initiation was prolonged due to the toughened layers. From damage observation, it was cleared that a transverse crack path to the thickness direction of the laminate was prevented by polyamide particles in the toughened layers. Therefore, it was found that the toughened layers dispersed polyamide particles to prevent delamination are effective for obstructing initiation of a transverse crack under cyclic loading.